Penguatan Usaha Mikro Berbasis Komunitas Arisan: Studi Kasus Kelompok Arisan Pelaku Usaha Mikro Muslim di Indonesia - Nurhidayah, Nurhidayah (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2025)
This study examines the arisan community as an instrument for strengthening micro-enterprises in Kebumen Regency. Through a qualitative approach with a case study on a micro-enterprise arisan group, this study identifies the mechanisms and dynamics that occur in the arisan community that contribute to the development of its members' micro-enterprises. The results of the study indicate that the arisan community not only functions as a socio-religious institution but also as a forum for fund circulation, a space for exchanging information, sharing best practices, knowledge, and social networks that facilitate strengthening the capacity of micro-enterprises. This arisan community-based empowerment model offers an alternative approach to local economic development that empowers communities, is inclusive, and sustainable. The practical implications of this study are useful for local governments and economic development institutions in formulating strategies for strengthening micro-enterprises based on community social capital. Keywords: micro-enterprise, arisan commmunity, economic empowerment, social capital